Mongo Beti, Ahmadou Kourouma and Ibrahima Ly: how feminists are they? (2011)
Mongo Beti’s Le Pauvre Christ de Bomba (1956) and Mission terminee (1957), Ahmadou Kourouma’s Les Soleils des independances (1970) and Ibrahima Ly’s Toiles d’araignee (1972) depict female characters confronted with traditional attitudes, religious prescriptions and patriarchal mores in Cameroonian, Ivorian and Malian societies. This article recognizes and applauds the attacks launched by Beti, Kourouma and Ly on certain Christian, Islamic and traditional African practices that subjugate sub-Saharan African women, even though these authors still portray their female characters as subaltern and women in bondage who aspire to free themselves from cultural enslavement and patriarchal domination.